PERAN STRUKTUR ORGANISASI OSIS SMP N 16 DALAM PENGEMBANGAN TIM YANG EFEKTIF - Utaminingsih, Sri; Akbar, Muhammad; Silalahi, Kristina; Hutagalung, Jeremi; Maretta, Loula; Nasiroh, Nasiroh (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
This activity examines the role of the OSIS organizational structure at SMP N 16 in developing an effective team in the context of community service events. A clear and planned OSIS organizational structure is an important foundation for improving member performance. Methods for Implementing Socialization Activities. The methods used in this socialization include interactive and practical approaches. Lecture Method The lecture method remains one of the main approaches in this socialization activity because it allows the delivery of information in a systematic and structured manner. Apart from providing theoretical exposure, the lecture method is also combined with visualization and other presentation tools to make it easier for participants to understand the material. This socialization aims to build and create an increased sense of responsibility for their respective roles in an effective organizational structure in every activity at school and outside school. It is hoped that this activity can become a reference for other schools in optimizing the function of student organizations.